SYSTEMATIC LITERATURE REVIEW: MINAT BERWIRAUSAHA PADA SISWA SEKOLAH MENENGAH KEJURUAN - Tananda, Opi; Rahman, Aulia; Sari, Bella Fitria; Ganefri, Ganefri; Yulastri, Asmar; Fiandra, Yudha Aditya (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
The aim of this literature review is to identify factors that have a significant influence on the interest in entrepreneurship among vocational school students. Taking into consideration the importance of vocational education as the principal method of finding employment and enhancing the national standard of living, understanding how to develop one’s career aspirations among such students becomes vital. Therefore, this review first defines the concept of vocational education in general and as a separate factor that helps students acquire certain skills for a particular job. Then, the focus is placed on individual factors such as characteristics of a person, external factors that shape one’s surroundings or stations may also have an influence on the willingness to engage in entrepreneurship. Environmental factors, including family background, socio-economic status, and cultural norms, also play a crucial role in shaping students' attitudes towards entrepreneurship. Positive role models, exposure to entrepreneurial experiences, and supportive educational environments are shown to foster entrepreneurial aspirations among vocational school students. Additionally, the review explores the impact of curriculum design and teaching methods on students' perceptions of entrepreneurship. Integrating entrepreneurship education into the curriculum, providing hands-on learning opportunities, and promoting real-world experiences are identified as effective strategies for stimulating interest in entrepreneurship among vocational school students. By synthesizing existing research, this review contributes to our understanding of how to nurture entrepreneurial talent among vocational school students, offering insights for educators, policymakers, and practitioners aiming to foster innovation and economic growth through entrepreneurship education. ABSTRAKTujuan dari kajian pustaka ini adalah untuk mengidentifikasi faktor-faktor yang memiliki pengaruh signifikan terhadap minat berwirausaha di kalangan siswa sekolah kejuruan. Dengan mempertimbangkan pentingnya pendidikan kejuruan sebagai metode utama untuk mencari pekerjaan dan meningkatkan standar hidup nasional, memahami cara mengembangkan aspirasi karier seseorang di kalangan siswa tersebut menjadi penting. Oleh karena itu, kajian ini pertama-tama mendefinisikan konsep pendidikan kejuruan secara umum dan sebagai faktor terpisah yang membantu siswa memperoleh keterampilan tertentu untuk pekerjaan tertentu. Kemudian, fokusnya ditempatkan pada faktor-faktor individu seperti karakteristik seseorang, faktor eksternal yang membentuk lingkungan atau kedudukan seseorang juga dapat memengaruhi kemauan untuk terlibat dalam kewirausahaan. Faktor lingkungan, termasuk latar belakang keluarga, status sosial ekonomi, dan norma budaya, juga memainkan peran penting dalam membentuk sikap siswa terhadap kewirausahaan. Teladan positif, paparan pengalaman kewirausahaan, dan lingkungan pendidikan yang mendukung telah terbukti menumbuhkan aspirasi kewirausahaan di kalangan siswa sekolah kejuruan. Selain itu, kajian ini mengeksplorasi dampak desain kurikulum dan metode pengajaran terhadap persepsi siswa tentang kewirausahaan. Mengintegrasikan pendidikan kewirausahaan ke dalam kurikulum, menyediakan kesempatan belajar langsung, dan mempromosikan pengalaman di dunia nyata diidentifikasi sebagai strategi yang efektif untuk merangsang minat dalam kewirausahaan di kalangan siswa sekolah kejuruan. Dengan mensintesis penelitian yang ada, tinjauan ini berkontribusi pada pemahaman kita tentang cara memelihara bakat kewirausahaan di kalangan siswa sekolah kejuruan, menawarkan wawasan bagi para pendidik, pembuat kebijakan, dan praktisi yang bertujuan untuk mendorong inovasi dan pertumbuhan ekonomi melalui pendidikan kewirausahaan.